Telomere Attrition With Concomitant hTERT Overexpression Involved in the Progression of Gastric Cancer May Have Prognostic and Clinical Implications in High-Risk Population Group From North India - Mushtaq, Ifra; Bhat, Gh Rasool; Rah, Bilal; Besina, Syed; Zahoor, Sheikh; Wani, Muneer A.; Shah, Mubashir A.; Bashir, Sadaf; Farooq, Muzamil; Rather, Rafiq A.; Afroze, Dil (Frontiers in Oncology, 2022)
Genetic instabilities exacerbated by the dysfunction of telomeres can lead to the development of cancer. Nearly 90 % of all human malignancies are linked with telomere dysregulation and overexpression of telomerase, an enzyme that catalyzes the synthesis of telomeric DNA repeats at the ends of chromosomes. The burden of gastric cancer continues to inflict a deterring impact on the global health scenario accounts for over one million new cases in 2020. The disease is asymptomatic in its early stages of progression attributing to the poor prognosis and overall surge in mortality rate worldwide. Exploiting the telomere physiology can provide a vast mechanistic insight in understanding the telomere-associated gastric cancer progression and its use as a target in diverse therapeutic interventions. In this study, we aimed to evaluate the clinical implications of c-MYC, hTERT expression and telomere length in the patients with gastric cancer. A total of 57 gastric cancer cases and adjacent controls were included in the study. RT-PCR and Immunohistochemistry was used to assess the expression levels of the c- MYC and hTERT. The relative telomere length was measured by MMQPCR using Cawthon method. Our results indicated that the shorter telomere and increased hTERT expression were associated with the gastric cancer progression. The study also highlighted the role of short telomeres and increased expression of hTERT in gastric cancer progression and its association with various etiological risk factors, transcriptional activators and overall survival among ethnic Kashmiri population of North India.